Raw materials and their technical role in the formal and functional system of the industrial product (Journal of the College of Basic Education, 2025)
The research deals with the research topic (Technical systems support formal and functional systems for product design). The importance of the research comes from the fact that the technical systems of materials have helped the designer in creating ideas to solve the problems he faces at the present time and have come to meet the needs and tendencies of society.Through this, the research objective was determined to identify how to set determinants for the forms and functions of industrial products in light of the technical systems for raw materials for the industrial product authority.The process of exploiting technical systems in industrial product manufacturing through their actual applications and leveraging them to solve various design problems of form and function that reflect the modern era, enables us to arrive at design foundations for effective integration of the functional and formal performance of the industrial product. The research sample was based on devices available at LG Company in 2021-2022.The research consists of five chapters. The first chapter deals with the research problem, its importance, objectives, and limits to the research topic. The research problem is embodied as follows: knowing the nature of the technical systems that support and influence the design systems of the forms and functions of the industrial product, as they are intertwined with each other for all design components....and the human desire for everything new and creative in terms of products or services within the technical systems that will be used in it, and it is necessary and inevitable to harmonize these innovations with the environment and preserve it at least if it is not possible to improve it.The second chapter included two sections on the theoretical framework. The first section included concepts related to technical systems for linking and production techniques and their relationship to the product form. The second section dealt with the design components that affect the formal and functional aspects of the product. The third chapter is the research methodology, the fourth chapter analyzes the research sample for three industrial products, and the fifth chapter showed several results. The most important results of the research were:1- The designer was able to use materials that carry symbols that express the designer’s idea with his basic intention, which is the limitation of building the product’s form that matches the output from which it was formed, through the use of materials that are compatible with the idea that the designer wants the product to belong to, in which the designer used materials with technical systems such as iron, aluminum, and plastics to express a specific idea related to his goal.2.Manufacturing processes played a role in addressing problems through the development of production methods using modern materials. They played a role in preserving the shape of the product to the minimum possible extent of suggestive elements according to the development of manufacturing processes in the design parts in accordance with the requirements of the era.3.By using modern materials such as transparent material to define the specific effect of the functional reception interface using liquid crystal material technology, which gave a great aesthetic and functional status to the functional reception interface.